MULTIPLE DRUG RESISTANCE IN AEROMONAS HYDROPHILA ISOLATES OF MUTTON - Kaskhedikar, M; Chhabra, D (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Fourteen antibacterial agents belonging to 9 different groups of antibiotics viz. aminoglycosides, cephalosporins, nitrofurantoin, fluroquinolones, chloramphenicol, sulphonamides, tetracyclines, penicillin and polymixin were used for in vitro sensitivity testing of two isolates of Aeromonas hydrophila isolated from fifteen samples of mutton, collected from retail shops in Mhow city. The sensitivity (100%) was attributed to ciprofloxacin, cefuroxime, ceftriaxone, cephotaxime, chloramphenicol, gentamycin, kanamycin, nitrofurantoin, nalidixic acid and ofloxacin followed by Co-trimoxazole (50%) and oxytetracycline (50%). All the isolates were resistant to ampicillin and colistin antibiotics. That means, none of the isolates were found to be sensitive for penicillin and polymixin group of antibiotics. Multiple drug resistance was also observed in all A. hydrophila isolates.
Keywords: MULTIPLE DRUG RESISTANCE; AEROMONAS HYDROPHILA; ISOLATES OF MUTTON